PEMAHAMAN PENTINGNYA GEMAR MENABUNG DALAM RANGKA MENGENALKAN INFORMASI KEUANGAN DAN PERTUMBUHAN UANG - Simangunsong, Ria Rosalia; Andhani, Destian; Suhartono, Agus; Nuryani, Anum; Abdi, Muhammad Zaenal Muttaqin (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of Community Service Activities is to carry out one of the Tri Darma of Higher Education. In addition, it is expected that through community service, the existence of tertiary institutions can make a major contribution to the development and application of knowledge to the community. The method used in this Community Service is in the form of counseling and coaching that is a better action, process, result, or statement. In this case shows progress, increased growth, evolution of various possibilities, develops or an increase in something. The results of community service obtained are increased knowledge for students and students conducted in grade 3 of the Department of Computer and Network Engineering at SMK Muhammadiyah Jl. H. Mawi No. 292 Desa Bojong Indah, Kec. Parung, Kab. Bogor 16330 with 25 participants, so that they have a good view of how motivated they learn, how to prepare themselves for entering college and the world of work. The knowledge gained in Community Service this time is expected to be able to provide new enthusiasm for us in delivering material and motivation to save and know the growth of money and to contribute to the young generation, both in schools, colleges, communities and families.